Analysis of Genetic Divergence in Tomato (Lycopersicon esculentum Mill.) - H R Sharma (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
Non-hierarchical analysis conducted on 60 genotypes of tomato (Lycopersicon esculentum Mill.) grouped the genotypes into 10 clusters. Maximum divergence within a cluster was exhibited by the cluster VIH (1.531), closely followed by cluster III (1.528) and cluster V (1.460), whereas, cluster VIII and cluster II were the most divergent from each other followed by cluster VII and cluster VIII. Promising genotypes selected were FT-5, LBR-10-2, THS-1-1, THS-2-2, T-99-1-2 and T-99-2-3 for yield per plant, fruit size index, pericarp thickness and plant height, whereas, W 55, Campbell and EC-123018 were found to be the best for average fruit weight. However, genotypes EC-170785 and Red cherry may be used to improve the number of fruits per plant and earliness.